Perlindungan Hukum Bagi Konsumen dalam Sengketa dengan Pelaku Usaha Pengembang Perumahan - Wibowo, Sigit (Jurnal Hukum Caraka Justitia, 2022)
The purpose of this study is to find out and examine why the form of legal protection for consumers in disputes with housing developers is still not optimal. The approach method used is normative juridical. This approach is intended to be a type of dogmatic research and a form of descriptive research concerning laws. Furthermore, the specification of this research is descriptive-analytical, namely by providing an overview of the problems raised and providing an analysis of the problem to be able to provide answers to these problems. Methods of data collection using library research that is testing the document materials and library materials used in this study. The data were analyzed qualitatively normative, namely conducting research by interpreting and constructing statements contained in statutory regulations. The thesis statement is that the Consumer Protection Act in the implementation of the protection of consumer rights has not been fully realized, mainly related to behavior to fight for rights, such as advocacy rights and the right to obtain compensation. The obstacles to implementation are related to factors that are not known in detail about the rights and obligations of the consumers. So housing consumer protection in the Consumer Protection Act had not played a role as expected when it was enacted, namely providing legal protection for consumer rights. This can be seen from the many violations related to buying and selling houses, where the parties who are greatly disadvantaged here are the housing consumers. Government control is still weak on business actors in the housing industry or developers, only limited to licensing alone, while regarding the interaction or direct relationship between developers and consumers, the government does not intervene.